Low molecular weight heparin as an adjunct to thrombolysis for acute myocardial infarction: the FATIMA study. Issue 1 (1st July 1998) - Chamuleau, S A J; de Winter, R J; Levi, M; Adams, R; Büller, H R; Prins, M H; Lie, K I; Peters, R J G
Abstract : Objective: To investigate the feasibility of fixed dose, weight adjusted subcutaneous low molecular weight heparin (LMWH), with monitoring of anti-Xa levels and assessment of coronary patency rates after three to five days, thereby giving an initial indication of its safety and efficacy. Design: In 30 patients with acute myocardial infarction, LMWH (nadroparine) was given as a body weight adjusted intravenous bolus with thrombolysis (rt-PA infusion) and in weight adjusted subcutaneous doses at six hours, and every 12 hours thereafter for 72 hours. The target range was defined prospectively as 0.35–0.70 anti-factor Xa activity (aXa) units. The aXa level was measured every six hours. Coronary angiography was performed in all patients within five days after the start of thrombolytic treatment to determine patency (TIMI 2 and 3 flow) of the infarct related artery. Results: The mean (SEM) aXa level over 72 hours was 0.52 (0.08) U/ml; from 12 hours onwards 88% of all aXa measurements were within the target range. At angiography, a patent infarct related artery was present in 24 of the 30 patients. No major bleeding complications occurred, though minor bleeding complications were observed in two patients. Conclusions: This small study indicates that LMWH is feasible as an adjunct to thrombolysis in patients with acute myocardial infarction. The aXa levels were within the target range and patency rates at three to five days were around 80%, with no major bleeding complications.